2017
DOI: 10.1007/s00264-017-3635-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thirty eight cemented pegged glenoid components with variable backside curvature: two-year minimum follow-up

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…11,24 Long-term results will determine if the use of new cemented pegged glenoid component with multiple backside curvatures can provide better results in terms of RLL and revision rates. 25 On the other side, McLeondon et al, in a long-term follow-up, with an average of 7.2 years, concluded that the risk of glenoid component failure (radiographic and clinical) was higher in pegged than keeled components. However, pegged design used in this study had liner pegs which are not the common design in the market.…”
Section: Glenoid Design Evolution For Pe Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,24 Long-term results will determine if the use of new cemented pegged glenoid component with multiple backside curvatures can provide better results in terms of RLL and revision rates. 25 On the other side, McLeondon et al, in a long-term follow-up, with an average of 7.2 years, concluded that the risk of glenoid component failure (radiographic and clinical) was higher in pegged than keeled components. However, pegged design used in this study had liner pegs which are not the common design in the market.…”
Section: Glenoid Design Evolution For Pe Implantsmentioning
confidence: 99%
“…Long-term results will determine if the use of new cemented pegged glenoid component with multiple backside curvatures can provide better results in terms of RLL and revision rates. 25…”
Section: All-pe Glenoidmentioning
confidence: 99%
“…Based on the findings of Walch et al, new glenoid component designs and reamers were developed with varying backside radiuses of curvature to match the patient's anatomy and to adapt the implant to the native bone and not vice versa. Promising shortterm results of those implant concepts have been published, but no long-term data are available yet [2,16].…”
Section: Discussionmentioning
confidence: 99%